Phytophthora nicotianae causing root and stem rot on dieffenbachia picta in Argentina - Palmucci, Hemilse Elena (2011)
Fil: Palmucci, Hemilse Elena. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Buenos Aires, Argentina.